Brucella : - Lopez-Goni, Ignacio (Horizon bioscience, 2004)
Horizon Scientific Press titles focus on high-level microbiology and molecular biology topics. Written by internationally renowned and highly respected leaders in the field, they comprise of review manuals, practical manuals, and reference texts for research scientists, bioscience professionals and graduate students. The book opens with chapters that focus on the development of molecular diagnostic tools followed by chapters on genetic evolution and its relationship to pathogenicity. Other topics include Brucella comparative genomics and proteomics, analysis of the structure, biosynthesis and biology of glucans and lipopolysaccharides, pathogenicity, approaches to vaccine development, bacterium-host interactions, immune response, and much more. Essential reading for everyone with an interest in Brucella and brucellosis and recommended reading for the wider body of scientists with an interest in microbial diagnostics, microbial pathogenesis, cellular microbiology and immunology, and vaccine development.